2016
DOI: 10.1186/s40728-015-0028-4
|View full text |Cite|
|
Sign up to set email alerts
|

Changing climate and its impacts on Assam, Northeast India

Abstract: The paper explores climate change induced hydro hazards and its impact on tribal communities in Majuli (largest river island of Brahmaputra River Basin). The island has been experiencing recurrent floods, erosion, and siltation, which has distressed the socio-economic foundation and livelihood of the Mishing—a indigenous community on Northeast India, leading to out migration from the island. The indicators selected to capture the vulnerability of the island to climate change are dependency ratio; occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…These precarious and temporary livelihood options are causing an increased vulnerability. Other studies have also shown that changes in precipitation may lead to unsustainable employment (e.g., Das, 2015 for northeast India; Hossain et al., 2020 for Bangladesh). The unpredictable nature of sedimentation also impedes human livelihoods and settlement, especially as residential areas adjacent to cultivated land are lost, and residents, particularly those living near hills and streams, are displaced from their original locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These precarious and temporary livelihood options are causing an increased vulnerability. Other studies have also shown that changes in precipitation may lead to unsustainable employment (e.g., Das, 2015 for northeast India; Hossain et al., 2020 for Bangladesh). The unpredictable nature of sedimentation also impedes human livelihoods and settlement, especially as residential areas adjacent to cultivated land are lost, and residents, particularly those living near hills and streams, are displaced from their original locations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Hail Haor, Bangladesh, Uddin et al (2013) found that the cultivation of various citrus fruits and pineapples accelerated soil erosion because farmers traditionally grew these fruits in rows aligned with the slope of the land, which promoted erosion. Similarly, Das (2015) and Ranjan (2019) point out that agricultural lands in India are one of the most significant sources of soil erosion and subsequent sedimentation in both wetlands and on river islands.…”
Section: Deforestation From Increased Agricultural Practicesmentioning
confidence: 99%
“…Government initiatives could greatly enhance the adaptive capacity of the farming communities (Ranjitkar et al, 2016;Jayakumar et al, 2017;Jiang et al, 2018;Rehman and Tanti, 2021). Promotion of alternative livelihoods such as eco-tourism and incorporation of indigenous traditional knowledge into community flood management are suggested to enhance social resilience to climate change in the BFP (Das, 2015). This review is expected to trigger the policy makers and scientists to accelerate mitigation policy formulation and arm the floodplain dwellers with devices to sustain their lives and livelihood in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct impacts, the agriculture sector is also likely to be indirectly affected by an increase in hydrometeorological hazards in future warming scenarios. Das (2015) reported that the frequency of climate change induced hydrological hazards such as flood, erosion, and siltation has increased in Majuli, the largest river island in the Brahmaputra River basin. This has devastated agricultural lands and declined farm productivity, forcing people to migrate to nearby cities in search of alternative livelihoods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation